AKTIVITAS FOSFATASE TANAH DILINGKUNGAN BENTANG HUTAN ALAMI DAN NON-ALAMI - Suliasih, Suliasih; Rahmansyah, Maman (BERITA BIOLOGI, 2009)
The spatial dispersal of acid and alkaline phosphates activity in forest soils appears to be controlled by position in the landscape and its soil microbial density. Soil bacteria expressively produced significant level of acid phosphatase in the investigation.The variety of acid phosphatase activity (8.25-37.55 />-nitrophenol.g"soil.h") noted higher and followed by alkaline (0.78-7.15 p-nitrophenol.g-soil.h" ), correspondingly. Acid and alkaline phosphates were exist in both of soil of natural as well as for non-natural forest soil landscape, with the value (po/o=0.6210) of correlation are 0.6889 and 0.6532, respectively. Phosphate Solubilizing Bacteria (PSB) average density in natural forest soil equivalent to 0.61xl0Ã colony forming unit (cfu) and total bacteria is 160xl0 cfu, while the PSB in non-natural forest soil is 7.75xl0 cfu and total bacteria is 48.25x10 cfu. Concerning to the forest environment as soil bacteria inhabitants of PSB, there were significantly difference of PSB population in natural and non-natural landscape forest. Forest environment is negatively affect the soil enzymes activities under Pinus maritima and Caliandra calothyrsus as the lowest activities, and to the highest ones under the Schima wallichii and Eucalyptus saligna vegetation.